Biochemical And Therapeutic Studies On Postparturient Indigestion (PPI) With Particular Reference To Hepatic Insufficiency In Buffaloes - K PADMAJA; D S T RAO (International Journal of Pharma and Bio Sciences, 2012)
Of 320 buffaloes within 60 days after calving, with the history of reduced feed intake and decreased milk yield presented, 90 (28.13%) buffaloes were found suffering with PPI. On detailed clinical examination and urinalysis, it was observed that 43 (47.78%) buffaloes had hepatic insufficiency. Out of 43 buffaloes of hepatic insufficiency, 23 (25.56 %) had hepatic insufficiency alone. Urine samples were positive for bile pigments. Serum samples were analysed for glucose, calcium, phosphorus, magnesium, total bilirubin, cholesterol, AST, GGT, total protein and albumin and compared with control buffaloes. Buffaloes with hepatic insufficiency were randomly divided in to two different groups. One group (n=11) animals were given Rintose at the rate of 0.5g/ kg b wt iv for one day and inj. Livadex Forte 10 ml im for 3 days. The second group (n=12) animals were given Rintose at the rate of 0.5g/ kg b wt iv for one day and inj. Toxol 10 ml im for 3 days. There was significant improvement in serum glucose, AST, GGT and calcium levels after the treatments and the therapeutic efficacy was found to be same.